The Prospects and Perils of Humanist Discourse - Martin, Terence J. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
The correspondence of Erasmus and Guillaume Budé represents an exemplary performance of the kind of intellectual exchange prized in humanistic circles of their day, though its sudden collapse has continued to puzzle interpreters. The design of this essay is to examine the prospects and perils of this epistolary venture set against the cultural, political, and religious circumstances of the time, and thus to show that this humanist project floundered not so much because of differences in personal character as due to fissures concealed in the rhetorical landscape over which these correspondents wished to travel. This rich and intricate theatre of humanist letters thereby illustrates both the noble aspirations and the inherent fragility of humanist discourse.